Cyclic stress-controlled tests on offshore clay - Thian S.Y.; Lee C.Y. (Chinese Academy of Sciences, 2023)
clay soil; cyclic loading; loading test; overconsolidation; pore pressure; shear strength; shear test; soil mechanics; stress; Malaysia